The development of "TAMENG" flipchart for eradication of anemia in pregnancy in Sumber, Kabupaten Probolinggo, Indonesia - Wardhana, Manggala Pasca; Sulistyono, Agus; Wahyuningtyas, Riska; Rahmatyah, Rizqy; Rosyada, Amrina; Rifdah, Salsabila Nabilah; Yusrika, Mirani Ulfa (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS The "TAMENG" flipchart significantly improved knowledge about anemia prevention among pregnant women. Nutritional status (mid-upper arm circumference) and history of anemia were strongly associated with anemia prevalence. Community-based, culturally relevant tools like the flipchart can effectively promote sustainable maternal health behaviors.   ABSTRACT Objective: This study aimed to evaluate the effectiveness of the "TAMENG" flipchart as an educational tool to improve knowledge about anemia prevention among pregnant women in Sumber, Kabupaten Probolinggo, Indonesia, and to explore associated risk factors for anemia, including nutritional status and supplementation practices. Materials and Methods: A community-based cross-sectional study was conducted in August 2024 as part of Universitas Airlangga’s Community Service Program. Pregnant women attending antenatal care in Sumber, Kabupaten Probolinggo were recruited based on ANC attendance and availability of hemoglobin test results. The "TAMENG" flipchart, designed with culturally relevant visuals and content on anemia prevention, was implemented during interactive education sessions. Demographic data, obstetric histories, and pre- and post-test knowledge assessments were collected. Statistical analysis was performed using chi-square tests to identify significant associations between variables. Results: Among 65 participants, 35.38% were anemic. Significant factors associated with anemia included nutritional status (60.9% of anemic women had mid-upper arm circumference <23.5 cm; p = 0.019) and history of anemia (30.4% vs. 9.5%; p = 0.032). Knowledge scores significantly improved post-intervention for 90.5% of non-anemic women and 100% of anemic women. Employment status and supplementation practices showed notable trends but were not statistically significant. Conclusion: The "TAMENG" flipchart effectively increased knowledge and awareness about anemia prevention. Tailored interventions addressing nutritional deficiencies, supplementation adherence, and family involvement can enhance maternal health outcomes in rural communities.